Flexible exchange rates and insulation: A reexamination - Joachim Fels (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Will a country embedded in an integrated world economy be able to completely insulate its economy from foreign economic disturbances by letting its currency float freely in the foreign exchange market? Both theoretical considerations and the actual experience after the movement to flexible exchange rates among the major currencies in 1973 suggest that the answer is no. According to conventional wisdom, however, the early advocates of flexible exchange rates in the 1950s and 1960s believed in the ability of floating rates to completely insulate an economy from disturbances originating abroad. This statement is frequently cited to show that the case for flexible exchange rates may not be as strong as it originally seemed to be, since part of the case appears to have rested on an erroneous belief. It is one purpose of this paper to point out that, contrary to a widespread view, the outstanding early advocates of flexible exchange rates like Milton Friedman (1953), Egon Sohmen (1961; 1969) and Harry Johnson (1969) never promised complete and automatic insulation from all kinds of foreign economic disturbances. In fact, their argument was more refined. The main purpose of the paper is to contrast Sohmen's true promise, as well as that of other theorists', with the empirical evidence from the period of floating exchange rates since 197 3 and to discuss several explanations for some remaining discrepancies between predictions and outcome.
Keywords: 330